Capturing the oxic transformation of iopromide – A useful tool for an improved characterization of predominant redox conditions and the removal of trace organic compounds in biofiltration systems?. (1st April 2019) - Müller, Johann; Jewell, Kevin S.; Schulz, Manoj; Hermes, Nina; Ternes, Thomas A.; Drewes, Jörg E.; Hübner, Uwe
Abstract: The biological degradation of many trace organic compounds has been reported to be strongly redox dependent. The traditional characterization of redox conditions using the succession of inorganic electron acceptors such as dissolved oxygen and nitrate falls short in accurately describing the critical transition state between oxic and suboxic conditions. Novel monitoring strategies using intrinsic redox tracers might be suitable to close that gap. This study investigated the potential use of the successive biological transformation of the iodinated contrast medium iopromide as an intrinsic tracer of prevailing redox conditions in biofiltration systems. Iopromide degradation in biofiltration systems was monitored by quantifying twelve known biological transformation products formed under oxic conditions. A novel dimensionless parameter (TIOP ) was introduced as a measure for the successive transformation of iopromide. A strong correlation between the consumption of dissolved oxygen and iopromide transformation emphasized the importance of general microbial activity on iopromide degradation. However, results disproved a direct correlation between oxic (>1 mg/L O2 ) and suboxic (<1 mg/L O2 ) conditions and the degree of iopromide transformation. Results indicated that besides redox conditions also the availability of biodegradable organic substrate affects the degree of iopromide transformation. Similar behavior was found for the compounds gabapentin and benzotriazole, while the oxic degradation of metoprolol remained stable under varying substrate conditions. Highlights: Successive biotransformation of iopromide in biofiltration systems. Substrate availability affects degree of iopromide biotransformation. No direct correlation between redox conditions and iopromide biotransformation. Different chemicals reveal individual degradation patterns in biofiltration systems.